Implementation of Character Building through General Subjects of Islamic Religious Education in STKIP Subang - Nahriyah Fata; Kama Abdul Hakam; Momod Abdul Somad; Yadi Ruyadi (IAIN Padangsidimpuan, 2023)
Optimizing the Role of Islamic Religious Education as a general compulsory subject that has a mission as education that shapes the character and cognitive development of students is a necessity. Therefore the research aims to examine how the policies of the STKIP Subang Elementary School Teacher Education Study Program in managing the General Course of Islamic Religious Education. Qualitative research through interviews, observation and documentation studies. This empirical research found: a lack of learning support facilities for Islamic Religious Education, time limitations, weaknesses in methods that are still oriented towards cognitive aspects, student backgrounds as heterogeneous inputs. As a compulsory subject for General Courses, Islamic Religious Education Courses must be packaged with newer pursuits even though the substance cannot be changed, but the current context must be answered through the internalization of Islamic values. The recommendations in this study are to carry out further research in the form of R and D research, stakeholder collaboration with managers, seeking creativity in learning innovations, etc. All of these recommendations are expected to have implications for improving the management of General Courses in Islamic Religious Education in the future.